2014
DOI: 10.2135/cropsci2013.08.0568
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Micronutrient Content of Cultivars of Field Pea, Chickpea, Common Bean, and Lentil Grown in Saskatchewan, Canada

Abstract: The mineral content of pulses grown in Saskatchewan, Canada, was examined for magnesium, potassium, iron, zinc, manganese, copper, selenium, and in some cases nickel and calcium. Eight to 18 cultivars of each of field pea (Pisum sativum), common bean (Phaseolus vulgaris), chickpea (Cicer arietinum), and lentil (Lens culinaris) were grown at several locations in southern Saskatchewan in 2005 and 2006 in randomized complete block designs with three replicates. Mineral content was examined by atomic absorption sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
92
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 22 publications
22
92
5
Order By: Relevance
“…Variation in grain Zn concentration among chickpea genotypes was previously reported (Khan et al, 2000;Kaya et al, 2009;Bueckert et al, 2011;Diapari et al, 2014;Ray et al, 2014). Responses to Zn applications were variable depending on the genotypes (Khan et al, 2000), which is not the case in our study.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Variation in grain Zn concentration among chickpea genotypes was previously reported (Khan et al, 2000;Kaya et al, 2009;Bueckert et al, 2011;Diapari et al, 2014;Ray et al, 2014). Responses to Zn applications were variable depending on the genotypes (Khan et al, 2000), which is not the case in our study.…”
Section: Discussionsupporting
confidence: 42%
“…In general, the micronutrient content of crops has received less attention and crop selection took place with little or no regard for the mineral and other micronutrient components of the seeds that may cover a very large part of the human diet (Ray et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil mineral composition has been well documented as the leading reason for differences in mineral composition in plants. Furthermore, Ray et al (2014) reported that, when different pulse species were grown at the same locations, some pulses accumulated more minerals. Furthermore, Ray et al (2014) reported that, when different pulse species were grown at the same locations, some pulses accumulated more minerals.…”
Section: Mineral Composition and Content Of Pulse Cropsmentioning
confidence: 99%
“…However, the four QTL for Mg and Ca seed concentrations reside on separate chromosome in Lotus japonicus (Blair et al 2009). There is a genotype by environment interaction for the seed mineral nutrient concentrations in pea, and further QTL study will be illuminating (Ray et al 2014).…”
Section: Discussionmentioning
confidence: 99%